Peran Etika Lembaga Yudikatif Dalam Mewujudkkan Keadilan Sosial: Perspektif Politik Islam - Firman Indra Jaya; Alfarisi, Muhammad Idris; Alfarisi, Kurniati (Jurnal Ilmu Pendidikan dan Sosial, 2024)
Social justice is one of the main pillars of Islamic teachings, which requires every individual and institution to uphold the values ​​of honesty, integrity and justice in every aspect of life. In Muslim-majority countries such as Indonesia, Malaysia and Saudi Arabia, the judiciary plays a key role in realizing social justice. However, corrupt practices, political interference and lack of competence often hinder the achievement of true justice. This research aims to analyze the role of judicial institution ethics in realizing social justice from an Islamic political perspective. The focus of this research is on Muslim-majority countries, particularly Indonesia, Malaysia and Saudi Arabia, to identify the extent to which Islamic values ​​are implemented in the judicial system and how this affects social justice. This research aims to analyze the role of judicial institution ethics in realizing social justice from an Islamic political perspective. The focus of this research is on Muslim-majority countries, particularly Indonesia, Malaysia and Saudi Arabia, to identify the extent to which Islamic values ​​are implemented in the judicial system and how this affects social justice. The results of this research provide recommendations for increasing the role of ethics in the judicial system in Muslim-majority countries in order to realize true social justice. Steps that need to be taken include systemic reforms to increase transparency and accountability, as well as strengthening legal education based on Islamic values.